The cultural tourism market in Portugal - Fernandes, Carlos (2007)
Tourism is increasingly offering a range of cultural products, from visiting monuments and traditional arts and crafts centres, to participating in historical events and discovering unique lifestyles. Tourism creates an interest in these particular forms of culture, often encouraging the preservation of cultural and historical traditions, contributing tothe protection of cultural heritage and to a renaissance of local cultures, cultural arts and crafts. The relationship between tourism and the cultural sector is potentially highly complementary. The cultural sector creates attractions for the tourist while tourism supplies extra audiences for cultural events and activities. Market segmentation coupled with target marketing is on the increase and cultural tourism could prove a worthwhile sector (Tighe, 1985).Because culture is the key and many times the primary reason for visiting certain tourist destinations, since 1992 theAssociation for Tourism and Leisure Education (ATLAS) has conducted surveys and acted as a Eurobarometer for cultural tourism in Europe (see www.geocities.com/atlasproject2004). ATLAS is an international association of higher education institutions and other organisations that promote transnational teaching and research of tourism, leisure and related subjects (www.atlas-euro.org).ATLAS carried out a worldwide survey in 2004, designed to gather information on the visitors to cultural events andattractions, including their holiday motivations, socio-demographic profiles and consumption patterns. In Portugal, the survey was carried out by several partners, under the coordination of the Laboratory of Tourism of the Polytechnic Institute of Viana do Castelo. This paper sets out to establish a profile of the cultural tourist in Portugal, based on the ATLAS survey at a wide range of different sites and types of attractions and locations in six of the seven tourism promotional regions of Portugal. The partners that took part in this survey were all volunteers. The Azores was the only region in which the survey was not conducted. Several local organisations were contacted, but none volunteered.